Multi level DC/DC converter design for DC micro grids - Shi, Donghan. (2013)
This report presents the design and simulation of a multi level DC-DC converter. The simulation was carried out using software Matlab. A key feature of the DC-DC converter is that it can generate output voltage of different levels. The software results of the voltage-based control of the DC-DC converter are presented.